Організація роботи бібліотек в умовах кризи, викликаної COVID-19: досвід Європи - Пономаренко, Зінаїда (Видавництво Львівської політехніки, 2020)
Various measures of European countries to impose quarantine and close libraries in the crisis situation COVID-19 are considered. Plans for the preparation of a gradual resumption of their work are highlighted.
Keywords: бібліотеки; короновірус; COVID-19; обмеження; цифрові ресурси; віддалений доступ